Proprioceptive rehabilitation strategies in posttraumatic wrist injuries. : Scoping review (Colombia Medica, 2024)
Background:The proprioceptive approach can effectively improve strength, mobility, edema reduction, and pain reduction, which in turn has a positive impact on functionality.Objective:To identify proprioceptive rehabilitation strategies reported in the literature in adults with traumatic wrist injuries.Methods:A scoping review was performed following the parameters of the Prisma ScR strategy. We included research with adult patients diagnosed with posttraumatic wrist injuries who used proprioceptive rehabilitation. Pain, functionality, strength, joint mobility ranges, and edema were evaluated.Results:After removing duplicates and applying the exclusion criteria, a total of 123 articles were found, which left six articles, including 125 patients. Rehabilitation protocols based on proprioceptive neuromuscular facilitation and using sensorimotor tools that promote wrist recovery have been generated. In addition, other approaches have been established, such as motor imagery, which generates a work of identification and organization of movement, improving pain and manual function. However, longer follow-ups, standardization of the instruments used during proprioceptive intervention, and increasing the observed population are needed to generate a recommendation for early intervention and cost-benefit estimates.Conclusions:Proprioceptive rehabilitation has demonstrated benefits in the recovery of the lower limb and hip or back. However, for the rehabilitation of traumatic wrist injuries, it is a research pending. Well-described data and good quality designs are needed to routinely propose this strategy in the clinic.